RsmW, Pseudomonas aeruginosa small non-coding RsmA-binding RNA upregulated in biofilm versus planktonic growth conditions - Miller, Christine L.; Romero, Manuel; Karna, S.L. Rajasekhar; Chen, Tsute; Heeb, Stephan; Leung, Kai P. (BioMed Central, 2016)
BACKGROUND: Biofilm development, specifically the fundamentally adaptive switch from acute to chronic infection phenotypes, requires global regulators and small non-coding regulatory RNAs (sRNAs). This work utilized RNA-sequencing (RNA-seq) to detect sRNAs differentially expressed in Pseudomonas aeruginosa biofilm versus planktonic state. RESULTS: A computational algorithm was devised to detect and categorize sRNAs into 5 types: intergenic, intragenic, 5′-UTR, 3′-UTR, and antisense. Here we report a novel RsmY/RsmZ-type sRNA, termed RsmW, in P. aeruginosa up-transcribed in biofilm versus planktonic growth. RNA-Seq, 5’-RACE and Mfold predictions suggest RsmW has a secondary structure with 3 of 7 GGA motifs located on outer stem loops. Northern blot revealed two RsmW binding bands of 400 and 120 bases, suggesting RsmW is derived from the 3’-UTR of the upstream hypothetical gene, PA4570. RsmW expression is elevated in late stationary versus logarithmic growth phase in PB minimal media, at higher temperatures (37°C versus 28°C), and in both gacA and rhlR transposon mutants versus wild-type. RsmW specifically binds to RsmA protein in vitro and restores biofilm production and reduces swarming in an rsmY/rsmZ double mutant. PA4570 weakly resembles an RsmA/RsmN homolog having 49% and 51% similarity, and 16% and 17% identity to RsmA and RsmN amino acid sequences, respectively. PA4570 was unable to restore biofilm and swarming phenotypes in ΔrsmA deficient strains. CONCLUSION: Collectively, our study reveals an interesting theme regarding another sRNA regulator of the Rsm system and further unravels the complexities regulating adaptive responses for Pseudomonas species.